SINTASAN LARVA UDANG GALAH DARI SUMBER GENETIK YANG BERBEDA - Ani Rimalia; Yulius Kisworo; Mukhlisah Mukhlisah (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2018)
This research aim to studi was to survival rate  of  the giant fresh water prawn from genetic resources pagatan river, Kintap river and Barito river.   The methot used this reserch was experimental design with completly random design (3X3). The results showed to the best survival rate from  genetic resources pagatan with SR=93,07%,  surviva rate genetic resources Barito with SR=90,40% and surviva rate genetic resources Kintap with SR=86,93%